Olivotourism as a tourist-cultural product and its influence on the dynamics of territories - Eunice Lopes; Pedro Martins (Via@)
This article proposes to explore olive tourism as a tourist-cultural product and its influence on the dynamics of territories. It is understood that the use of natural and cultural resources existing in the territories, as differentiating tourist products, when coherent and rigorous, can be the key factor for territorial cohesion and sustainability. The practice of olive tourism is strongly linked to the tourist and cultural development of more natural and rural areas, contributing to the appreciation and conservation of the unique identity of places, through the promotion of traditional activities that can be experienced by tourists. In this sense, product development strategies based on olive oil and olive trees are relevant to enhance knowledge of the product itself and its connection with local history and traditions. The increase in olive tourism is presented in this study as a challenge for the territory (municipality of Idanha-a-Nova, Portugal), highlighting the recovery of some activities that have been developed to revitalize territorial cohesion.